Biophysical regions of the Southern Highlands, Tanzania - Koskikala, Joni; Kisanga, Danielson R; Käyhkö, Niina (PANGAEA, 2019)
Biophysical regionalization of the Southern Highlands area of Tanzania based on open source global environmental datasets depicting climate, soil, topography and vegetation.
Keywords: Africa; Global South; Regionalization